Are retailers compliant with zoning regulations that ban tobacco sales near schools in Changsha, China?. Issue 4 (25th July 2016) - Wang, Ling; Lu, Bo; Wewers, Mary Ellen; Foraker, Randi E; Xie, Mengyao; Ferketich, Amy K
Abstract : Background: Tobacco retail sales are prohibited within 100 m of schools in many large cities in China. However, little is known about the enforcement of this zoning regulation. The objectives of this study were to estimate tobacco retailers' compliance with the regulation, examine the density of tobacco retail stores, describe the types of tobacco products sold in stores and how they are marketed, and determine if there are displays of warning messages in retail stores around schools and in neighbourhoods in Changsha, China. Methods: Tobacco retail stores located within 200 m of 36 schools and 36 residential neighbourhoods were audited by trained students with a validated audit form. Results: On average, there were about 3 tobacco retail stores within 100 m of the front entrance of schools. The density of the stores and the types of tobacco products sold in the stores were similar near schools and in neighbourhoods. Over one-fourth of the stores had exterior tobacco advertisements. Interior advertising was slightly less prevalent, and it was most prevalent among tobacco shops (62.5%). Tobacco displays that target children were pervasive, with about 83% of tobacco retail stores displaying cigarettes within 1 m of the floor and 59% displaying cigarettes within 0.3 m of toys and candy. About 40% of stores within 100 m of a school had a visible retail licence. Only 19.6% of the stores had a 'smoke-free' sign and 22.2% had a 'no sales to minors' sign. Conclusions: We observed low enforcement of the regulation that bans tobacco retail sales near schools and high prevalence of tobacco displays that target children in Changsha, China. Chinese officials should act to effectively enforce the regulation bans of tobacco sales near schools. In addition, regulations are urgently needed to limit tobacco marketing practices at the point of sale, especially those targeting youth.